Characteristics and Predictors of Outcome of Pseudoaneurysms Associated With Vertebral Artery Dissections: A 310-Patient Case Series. Issue 5 (15th January 2021) - Shlobin, Nathan A; Azad, Hooman A; Mitra, Akash; Prasad, Nikil; Cloney, Michael B; Hopkins, Benjamin S; Jahromi, Babak S; Potts, Matthew B; Dahdaleh, Nader S
Abstract: BACKGROUND: Vertebral artery dissections (VADs) are a common cause of stroke in young patients and can result in various secondary effects, including pseudoaneurysm formation. OBJECTIVE: To identify differences in predisposing factors and outcomes for VADs with and without concomitant pseudoaneurysms. METHODS: We retrospective chart reviewed patients who presented to our institution at the time of VAD with at least a 3-mo clinical follow-up. Demographics, VAD characteristics, treatment, and outcomes represented as modified Rankin scale (mRS) scores were collected. RESULTS: Of 310 patients with a VAD included in this study, 301 patients had an identified pseudoaneurysm status, with 54 pseudoaneurysm-associated VADs and 247 VADs not associated with pseudoaneurysm. VAD patients with associated pseudoaneurysms were more likely to be female ( P  < .004), have bilateral VADs ( P  < .001), and have fewer vertebral artery segments affected ( P  = .018), and less likely to have stroke ( P  < .008) or occlusion of the vertebral artery ( P  < .001). There was no difference in the proportion of patients treated with antiplatelet agents ( P  = .12) or anticoagulants ( P  = .27) between the groups. VAD patients with associated pseudoaneurysms were more likely to have a higher mRS at 3-mo follow-up ( P  = .044) but not discharge ( P  = .18) or last follow-up ( P  = .05). VAD patients with pseudoaneurysms were equally likely to have resolution of occlusion ( P  = .40) and stenosis ( P  = .19). CONCLUSION: Demographics and clinical and radiological characteristics of VADs associated with pseudoaneurysms are different from those without associated pseudoaneurysms. Vertebral artery dissections with concomitant pseudoaneurysms are neither associated with worse functional nor radiographic outcomes.